Association between composite lifestyle factors and cardiometabolic multimorbidity in Chongqing, China: A cross-sectional exploratory study in people over 45 years and older - Yuanjie Zheng; Yuanjie Zheng; Yuanjie Zheng; Zhongqing Zhou; Zhongqing Zhou; Zhongqing Zhou; Tingting Wu; Tingting Wu; Kailuo Zhong; Kailuo Zhong; Kailuo Zhong; Hailing Hu; et al. (Frontiers Media S.A., 2023)
IntroductionModifiable lifestyle factors are considered key to the control of cardiometabolic diseases. This study aimed to explore the association between multiple lifestyle factors and cardiometabolic multimorbidity.MethodsA total of 14,968 participants were included in this cross-sectional exploratory study (mean age 54.33 years, range 45-91; 49.6% male). Pearson's Chi-square test, logistic regression, and latent class analysis were employed.ResultsWe found that men with 4-5 high-risk lifestyle factors had a 2.54-fold higher risk (95% CI: 1.60-4.04) of developing multimorbidity compared to males with zero high-risk lifestyle factors. In an analysis of dietary behavior, we found that in women compared to men, over-eating (OR = 1.94, P < 0.001) and intra-meal water drinking (OR = 2.15, P < 0.001) were more likely to contribute to the development of cardiometabolic multimorbidity. In an analysis of taste preferences, men may be more sensitive to the effect of taste preferences and cardiometabolic multimorbidity risk, particularly for smoky (OR = 1.71, P < 0.001), hot (OR = 1.62, P < 0.001), and spicy (OR = 1.38, P < 0.001) tastes. Furthermore, "smoking and physical activity" and "physical activity and alcohol consumption" were men's most common high-risk lifestyle patterns. "Physical activity and dietary intake" were women's most common high-risk lifestyle patterns. A total of four common high-risk dietary behavior patterns were found in both males and females.ConclusionsThis research reveals that the likelihood of cardiometabolic multimorbidity increases as high-risk lifestyle factors accumulate. Taste preferences and unhealthy dietary behaviors were found to be associated with an increased risk of developing cardiometabolic multimorbidity and this association differed between genders. Several common lifestyle and dietary behavior patterns suggest that patients with cardiometabolic multimorbidity may achieve better health outcomes if those with certain high-risk lifestyle patterns are identified and managed.